Development Material Teach for Improving The Ability to Speak In Indonesian - Juliana, Eva (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Study This aim For develop And evaluate effectiveness module learning in increase ability speak in Language Indonesia on student class 9 JUNIOR HIGH SCHOOL Country 3 Padangsidimpuan. Approach study use design development (RD) with models ADDIE (Analysis, Design, Development, Implementation, Evaluation). the module designed For facilitate learning independent students and strengthen Skills speak. Research result show that use module learning in a way significant increase ability speak student. The results of data analysis from the pre-test and post-test show enhancement score ability speak significant students in a way statistics. Additionally, students respond positive to module this, with part big from they feel more motivated And believe self in speak Language Indonesia. Importance the role of the teacher in implementation module is also proven important in reach success learning. Teacher Which trained and involved active in learning can increase effectiveness module. By Because That, training Teacher become factor key in integration module in learning. In conclusion, use module developed learning with the ADDIE model is effective in increase ability speak student in Indonesian. this module No only help in understanding material, but also encouraging interest and motivation student in learning Indonesian . Study This give base for development more carry on in Indonesian language teaching and providing contribution in effort increase effectiveness learning speak. Learning module This can become source Power valuable in context Indonesian language education.